A Modified Technique for Extraction Site Closure of the Maxillary Molars in a Dog. (March 2018) - Ritchie, Curt
Performing oral surgery in dogs can present unique challenges. Among those challenges are the varying size and anatomical shape of the oral cavity in veterinary patients. Very small dogs and brachycephalic breeds provide limited exposure to the caudal maxilla. With the addition of an endotracheal tube and tie, the operating window can be quite limited and difficult to visualize and instrument. The following is a simple yet effective step-by-step procedure of tension-free closure of maxillary molar extractions in the dog.